123k views
3 votes
Subtract these polynomials and simplify. Enter your response in standard form. (2 − 4x9 + 3x3) − (7x + x3 − 6 + 12x4)

User Suvekshya
by
6.1k points

2 Answers

4 votes

Answer:


Explanation:

(2 − 4x9 + 3x3) − (7x + x3 − 6 + 12x4)


= 2 − 4x9 + 3x3 − 7x − x3 + 6 − 12x4


= -4x9 − 12x4 + 3x3 − x3 − 7x + 2 + 6


= -4x9 − 12x4 + 2x3 − 7x + 8

User David Lovell
by
5.9k points
5 votes

2 - 4x⁹ + 3x³ - (7x + x³ - 6 + 12x⁴)

= 2 - 4x⁹ + 3x³ - 7x - x³ + 6 - 12x⁴

= (2 + 6) + (-4x⁹) + (3x³ - x³) + (-7x) + (-12x⁴) grouped like terms

= 8 - 4x⁹ +2x³ -7x -12x⁴ added like terms

= - 4x⁹ - 12x⁴ + 2x³ - 7x + 8 standard form

User Manas Chaturvedi
by
6.3k points